KETERKAITAN KEBIJAKAN PEMISAHAN TERHADAP TINGKAT EFISIENSI PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - M. Nur Rianto Al Arif (Jurnal Keuangan dan Perbankan, 2015)
One way to accelerate the growth of Islamic banks in Indonesia was by applying the policy of separation. Thepurpose of this study was to analyze the relationship between separation policy that had been implementedsince 2008 with the operational efficiency of the Islamic banking industry in Indonesia. The method used wasregression with dummy variables. The variables used in this study were a dummy variable separation,deposits, financing, assets, NPF, margin deposits of one month, and ROA. The result showed that separationpolicy had a relationship with the operational efficiency on Islamic banking industry in Indonesia. This resultimplied that separation policy should have been evaluated because it caused the industry to be less efficientwhen compared with the condition before the separation.